Scheduling of nutrient doses for rough lemon (Citrus jambhiri) rootstock under containerized primary and secondary nursery - MARATHE, R A; MURKUTE, A A; SONKAR, R K; LADANIYA, M S; KOLWADKAR, JAYSHREE; DESHPANDE, CHAITANYA (The Indian Journal of Agricultural Sciences, 2021)
The study was carried out to investigate and standardize the nutritional requirement of commonly used roughlemon (Citrus jambhiri Lush) citrus rootstock for raising commercial primary and secondary containerized nursery.The aim of the study was also to reduce fairly high (2 years) time required traditionally for seedling production incitrus nurseries and to provide healthy seedlings. Two separate experiments, comprising different nutrient doseswere conducted under primary and secondary containerized nursery. The results revealed that dry weight of all theplant parts and number of leaves was maximum with the application of 40+25+25 g NPK. Uptake of all the macronutrients,viz. N (31.2 mg), P (1.33 mg) and K (27.7 mg) by the plants was also highest under this treatment. Whileplant height and leaf chlorophyll contents were better in 20+10+10g NPK as compared to control. In secondarynursery, application of 4+2+2 g NPK recorded maximum plant height, stem girth, budding success rate (95.8%) andsignificantly reduced the time required for budding. Although availability of major nutrients was significantly highestin 60+25+25 g NPK treatment, it could not encourage the growth of the plants and induced plant mortality. In primarynursery, application of 40+25+25 g NPK and in secondary nursery, application 4+2+2 g NPK potting mixture wereproved to be the superior nutrient dosage for rough lemon rootstock.